Design of a Mechanised Sorghum Sieving Machine Used in Agriculture Production. - Amanya, Davis (Kabale University, 2025)
This study was formulated to design and simulate a mechanized sieving machine for sorghum, incorporating a detailed study of existing designs and utilizing SolidWorks software for conceptualization. The methods involved desk review by comparing the existing specifications with the mode of operations, and interviews through direct interviews with local farmers about the capacity of their product. Observations going to the field and observing the farmer's produce per day, questioners asking questions about income and what can be the affordable price for the machine The objectives involved determining the design specification of the sieving machine, selecting and sizing the sieving machine to meet the design specifications, developing the layout of the machine, evaluate the performance of the machine through simulation. The working principle caters to the transmission of motor rotation to a driving pulley, controlling speed through a driving belt, and converting rotary motion to linear motion using a crank mechanism. Detailed sizing yielded key parameters such as sieve volume, height, output force, rotation speed, torque, power, crank length, connecting rod length, and sieve velocity. The results were verified through simulation using Ansys software, confirming the accuracy and efficiency of the proposed design. The mode of operation involves the transmission of motor rotation to a driving pulley, controlled by a driving belt, resulting in a reciprocating motion of the sieve through a crank mechanism. Comprehensive sizing of key components, including the sieve, crank, connecting rod, pulleys, and belt, was conducted, leading to a successful simulation using Ansys software. The simulation results verified the design's integrity and efficiency, ensuring its suitability for sorghum sieving applications. The detailed results include the volume and height of the sieve, output force, rotational speed of the driven pulley, torque, power requirements, and various dimensions of the mechanical components. These results were found to align successfully with the intended specifications, providing confidence in the feasibility and effectiveness of the proposed design. In conclusion, the project achieved its objectives by presenting a well-conceived and simulated sorghum sieving machine design. The proposed material selections ensure durability, efficiency, and ease of maintenance, while the simulation results validate the machine's performance under realistic conditions. Recommendations include further prototype testing, material optimization, user feedback integration, and considerations for energy efficiency and scalability. This project contributes valuable insights to the field of agricultural machinery design, with potential applications in enhancing sorghum processing efficiency.